2018
DOI: 10.1016/j.idcr.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal histoplasmosis: The diagnosis lies in the biopsy

Abstract: Histoplasma capsulatum, a dimorphic fungus found world-wide, is endemic to regions of the Mississippi and Ohio River valleys and portions of Central and South America. Initial infection can present with acute pulmonary symptoms or remain clinically asymptomatic, with disease course generally guided by degree of inoculum and underlying immunosuppression. A chronic, progressive course of weight loss, oral ulceration, and fatigue has been associated with elderly males. We present a 79-year-old man with a chronic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…Histoplasmosis caused by Histoplasma capsulatum usually occurs after exposure to bird and bat guano [ 6 ]. After inhalation of microconidia, it may cause pulmonary involvement, presenting as pneumonia, or may remain asymptomatic [ 7 ]. However, immunodeficiency patients can develop a disseminated disease involving the bone marrow, adrenal glands, gastrointestinal system, and reticuloendothelial system [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Histoplasmosis caused by Histoplasma capsulatum usually occurs after exposure to bird and bat guano [ 6 ]. After inhalation of microconidia, it may cause pulmonary involvement, presenting as pneumonia, or may remain asymptomatic [ 7 ]. However, immunodeficiency patients can develop a disseminated disease involving the bone marrow, adrenal glands, gastrointestinal system, and reticuloendothelial system [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only a single case (2.04 %) of nasopharyngeal masses was diagnosed as histoplasmosis 15 . Claudia Miranda et al 6 , in 2018, reported a case of a 79-yearold male presenting with odynophagia, dysphagia, fever and weight loss. The CT scan showed diffuse thickening of the oropharynx, supraglottic larynx, extending up to the vocal cords.…”
Section: Discussionmentioning
confidence: 99%
“…Histoplasmosis is found worldwide and is endemic in regions of Latin America and North America, Europe and few regions of Asia. In India, Histoplasmosis is endemic in Gangetic Delta of West Bengal and Assam 1,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Histoplasmosis is a dimorphic fungus which is known to be widely distributed among western countries like America and in some parts of the tropical region. 1 In North America Histoplasma capsulatum is endemic to the Mississippi and Ohio River valleys but is also present in other areas. 2,3 There are two different type of fungus Histoplasma capsulatum var.…”
Section: Introductionmentioning
confidence: 99%